PROFIL GARIS PALMAR DAN SUDUT AXIAL TRIRADIUS DIGITAL PADA SISWA BERKEBUTUHAN KHUSUS DI KOTA BENGKULU - Kamilah, Santi Nurul; Manurung, Widya C.; Lestari, Dian Fita; Haryanto, Hery; Sipriyadi, Sipriyadi; Muslim, Choirul (BIOMA : JURNAL BIOLOGI MAKASSAR, 2024)
Each individual is unique, one of which is the palmar line pattern on the surface of the palm skin. Children with special needs from the Down syndrome tend to have a Simian pattern. The purpose of this study was to analyze the palmar line and the angle of Axial Triradius Digital (ATD) on the palms of special needs students from the deaf, deafblind, and physically disabled groups at Sekolah Luar Biasa (SLB) Negeri 1 Bengkulu City. This research was conducted in September-October 2021 using interview and direct data collection methods on students who met the inclusion requirements. The results indicated that three distinct palmar patterns were observed in the three groups of students. The most prevalent pattern was the normal pattern, which was observed in 84.8% of deaf students, 70.4% of retarded students, and 83.3% of disabled students. The ATD of 350-500 was the most prevalent angle for entire groups of students: 87% of the deaf students, 84.3% of the deafblind students, and 100% of the physically disabled students. Furthermore, the Chi-Square test demonstrated that there was no relationship between palmar line patterns, ATD angles, and the group of special needs students. Keywords: Axial Triradius Digital (ATD) angles, Palmar, Student with special needs